Defoliation of two-wire vertical trellis: effect on grape quality. Issue 1 (2nd January 2018) - Scafidi, P.; Barbagallo, M. G.; Pisciotta, A.; Mazza, M.; Downey, M. O.
ABSTRACT: Basal leaves were removed from Cabernet Sauvignon vines trained to a two-wire vertical trellis at fruit set and at veraison. Leaf removal did not modify total soluble solids and titratable acidity at harvest. Defoliation at fruit set of lower cordon recovered the grape anthocyanin composition gap between upper and lower cordons and that produced a positive effect on anthocyanin synthesis. Hence, control of the upper cordon and defoliation of fruit set of the lower cordon treatments showed comparable values of anthocyanins. Defoliation at veraison did not produce any appreciable effect. This study shows that skin anthocyanin composition in a two-wire vertical trellis can be modified by leaf removal in the fruit zone of the lower cordon, reducing variability in the ripeness between the two cordons.